2019
DOI: 10.1101/510446
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variation inMelitaea cinxiagut microbiota is phylogenetically highly structured but only mildly driven by host plant microbiota, sex or parasitism

Abstract: Originality-Significance StatementThe factors contributing to the assembly of microbiota in animals are extremely complex, and thus a comprehensive understanding of the mechanisms shaping host-associated microbial communities in natural ecosystems requires extensive ecological studies and appropriate statistical methods. In this study, we investigated the bacterial microbiota associated with the caterpillars of the Glanville fritillary (Melitaea cinxia), which is a long-term-studied ecological model system. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 100 publications
1
9
0
Order By: Relevance
“…So, the variability observed among the different greenhouses could be attributed to differences in foliar microbiota of each pepper plant and the greenhouse soil microbiota in which the caterpillars were collected. This explanation is also supported by previous studies in which the larval gut bacteria did not totally correspond with dietary associated leaf bacteria (Whitaker et al, 2016;Hammer et al, 2017;Minard et al, 2019). Thus, the authors suggested larval gut microbiota is composed of transient bacteria instead of resident microbiota, due to the intrinsic insect gut physiology, such as their high pH, simple tube structure, and rapid digestion that prevent gut colonization by bacterial uptake with food (Hammer et al, 2017).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…So, the variability observed among the different greenhouses could be attributed to differences in foliar microbiota of each pepper plant and the greenhouse soil microbiota in which the caterpillars were collected. This explanation is also supported by previous studies in which the larval gut bacteria did not totally correspond with dietary associated leaf bacteria (Whitaker et al, 2016;Hammer et al, 2017;Minard et al, 2019). Thus, the authors suggested larval gut microbiota is composed of transient bacteria instead of resident microbiota, due to the intrinsic insect gut physiology, such as their high pH, simple tube structure, and rapid digestion that prevent gut colonization by bacterial uptake with food (Hammer et al, 2017).…”
Section: Discussionsupporting
confidence: 64%
“…In addition, previous Lepidoptera studies revealed apparent contradictions with respect to diet influence on gut microbiota. Some studies claimed diet significantly influenced lepidopteran gut microbiota composition (Yun et al, 2014;Berman et al, 2018;Phalnikar et al, 2018;Jones et al, 2019), whereas other authors reported diet had little or no effect on microbiota (Whitaker et al, 2016;Chaturvedi et al, 2017;Minard et al, 2019). This apparent contradiction seems to reveal the lack of caterpillar specific gut microbiota as reported by Hammer et al (2017).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…While the computational costs of the earlier JSDMs were intractable for microbial data, it is now possible to handle hundreds of taxa and samples in a reasonable time (Tikhonov et al ., 2020a; Tikhonov et al ., 2020b). A few recent studies applied JSDMs to investigate spatial patterns in microbiota (Björk et al ., 2018; Aivelo et al ., 2019; Minard et al ., 2019). In particular, a recent study adapted JSDMs to microbiota by incorporating host phylogeny and traits and illustrated this development on bird and sponge microbiota (Björk et al ., 2018).…”
Section: Spatial Modelling Frameworkmentioning
confidence: 99%
“…This study demonstrates the use of JSDMs to partition variance between spatial effects and host‐related factors and to obtain co‐occurrence networks. A study conducted on caterpillar microbiota revealed phylogenetic structuring in the communities, with related microbial taxa exhibiting similar patterns (Minard et al ., 2019). The communities displayed high variation between individual caterpillars, on which neither the host‐ and host plant‐related factors nor spatial structure appeared to have significant influence.…”
Section: Spatial Modelling Frameworkmentioning
confidence: 99%